Computer-aided control system design at Cornell: Student reaction is positive to the incorporation of emerging computer-aided control system design (CACSD) software in the teaching of introductory control systems theory in the School of Electrical Engineering at Cornell University - Johnson, C. Richard; Nakamuta, Tetsuya (IEEE potentials, 1985)
A popular course in most electrical engineering curricula is control systems theory. It is one of the prominent extensions of the theoretical core of network theory. At most universities the emphasis in control systems theory courses is on computationally intensive analysis and design, which are at the heart of control engineering. Over the last few years, an increasing number of university and industrial researchers have been exploiting the power of the computer to perform such sequences of computation and data display needed in control system design. These computer aids in the control system design and simulation process have allowed these engineers to focus their efforts more substantially on the complex decisions needed in the selection of an appropriate controller.